Cyclic AMP Promotes Neuronal Survival by Phosphorylation of Glycogen Synthase Kinase 3β - Li, Mingtao (American Society for Microbiology, 2000)
Agents that elevate intracellular cyclic AMP (cAMP) levels promote neuronal survival in a manner independent of neurotrophic factors. Inhibitors of phosphatidylinositol 3 kinase and dominant-inactive mutants of the protein kinase Akt do not block the survival effects of cAMP, suggesting that another signaling pathway is involved. In this report, we demonstrate that elevation of intracellular cAMP levels in rat cerebellar granule neurons leads to phosphorylation and inhibition of glycogen synthase kinase 3β (GSK-3β). The increased phosphorylation of GSK-3β by protein kinase A (PKA) occurs at serine 9, the same site phosphorylated by Akt. Purified PKA is able to phosphorylate recombinant GSK-3β in vitro. Inhibitors of GSK-3 block apoptosis in these neurons, and transfection of neurons with a GSK-3β mutant that cannot be phosphorylated interferes with the prosurvival effects of cAMP. These data suggest that activated PKA directly phosphorylates GSK-3β and inhibits its apoptotic activity in neurons.